2021
DOI: 10.1177/22808000211065260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Streptococcus mutans on surface-topography, microhardness, and mechanical properties of contemporary resin composites

Abstract: Objective: Dental caries is the most prevalent disease globally, and Streptococcus mutans ( S. mutans) is a common associated oral bacteria. Additionally, S. mutans possess esterase activity capable of degrading resin composites (RC). However, the effect of degradation on the physical-mechanical properties of the RC has not been extensively studied. We evaluated the flexure strength (FS), the diametral tensile strength (DTS), the modulus of elasticity (ME), and the microhardness of three contemporary RC to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“… 43 In addition, bacterial esterase can also increase the shrinkage of methacrylate resin and reduce the mechanical properties of the material, such as hardness, bending strength, radial tensile strength and elastic modulus. 45 With an increase in the roughness of a resin attachment surface, adhesion of bacteria increases, and consequently the esterase that the bacteria produce enhanced biodegradation.…”
Section: Water Attack and Hydrolytric Degradation Of Aligners And Att...mentioning
confidence: 99%
“… 43 In addition, bacterial esterase can also increase the shrinkage of methacrylate resin and reduce the mechanical properties of the material, such as hardness, bending strength, radial tensile strength and elastic modulus. 45 With an increase in the roughness of a resin attachment surface, adhesion of bacteria increases, and consequently the esterase that the bacteria produce enhanced biodegradation.…”
Section: Water Attack and Hydrolytric Degradation Of Aligners And Att...mentioning
confidence: 99%
“…When the Bis-GMA-based resin was co-cultured with S. mutans , it was found that S. mutans considerably enhanced the surface roughness of the resin composite [ 38 ], and Bis-HPPP could be detected after 14 days [ 37 ]. In addition, bacterial esterase can also increase the shrinkage of methacrylate resin and reduce the mechanical properties of the material, such as microhardness, bending strength, radial tensile strength and elastic modulus [ 39 , 40 ]. When the surface of the resin becomes rough, the adhesion of bacteria increases.…”
Section: Factors Causing Biodegradationmentioning
confidence: 99%